Core–shell Cu@(CuCo-alloy)/Al2O3 catalysts for the synthesis of higher alcohols from syngas. Issue 3 (16th December 2014) - Gao, Wa; Zhao, Yufei; Chen, Haoran; Chen, Hao; Li, Yinwen; He, Shan; Zhang, Yingkui; Wei, Min; Evans, David G.; Duan, Xue
Abstract : Core–shell Cu@(CuCo-alloy)/Al2 O3 catalysts are obtained via an in situ growth–calcination–reduction process, which exhibit excellent catalytic behavior toward CO hydrogenation to produce higher alcohols. Abstract : The production of higher alcohols by the catalytic conversion of synthesis gas (CO + H2 ) is one of the most promising approaches for the utilization of nonoil resources, in which bimetallic catalysts based on Cu and Fischer–Tropsch (FT) reaction active elements ( e.g. Co, Fe, Ni) are efficient and cost-effective candidates. Herein, we demonstrate the fabrication of core–shell Cu@(CuCo-alloy) nanoparticles (NPs) embedded on a Al2 O3 matrix via an in situ growth of CuCoAl-LDH nanoplatelets on aluminum substrates followed by a calcination–reduction process, and they serve as efficient catalysts toward CO hydrogenation to produce higher alcohols. The composition, particle size and shell thickness can be tuned by changing the Cu/Co molar ratio in the LDH precursors, and the best catalytic behavior was obtained over the Cu/Co (1/2) catalyst with a CO conversion of 21.5% and a selectivity (C6+ slate 1-alcohols) of 48.9%, which is superior to the traditional modified FT catalysts. XPS, in situ FTIR spectroscopy and HAADF-STEM revealed that the unique electronic and geometric interaction between Cu and Co in the Cu@(CuCo-alloy) NPs contributes to the significantly enhanced catalytic performances. In addition, the 3D hierarchical structure of the Cu@(CuCo-alloy)/Al2 O3 catalyst facilitates mass diffusion/transportation as well as prevents hotspot formation, accounting for its stability and recyclability. The Cu@(CuCo-alloy)/Al2 O3 catalyst with significantly improved catalytic behavior can be potentially used in CO hydrogenation to produce higher alcohols.